Charging dynamics in a low-dimensional doped thermoelectric - Абуова , Ф. У.; Inerbaev , T. M.; Абуова , А.; Сазанбай , А.; Нураканов , А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Materials that convert heat into electricity are needed to tackle global warming and other climate concerns. Thermoelectric nanowires are new metamaterials for such applications. Non-adiabatic bond calculations are critical to understanding thermally activated charge transfer in thermoelectric materials. In this work, the calculations of nonadiabatic electron dynamics are used to estimate the electron relaxation rates in lead telluride nanowires. The calculations were performed on the basis of the ground state density functional theory. State transitions are modeled in terms of the Redfield equation of motion, parametrized on the fly by non-adiabatic constraints along the thermalized path of molecular dynamics. The initial and excited states are approximated by the advancement of an electron from an occupied to an unoccupied Kon-Sham orbit. With each transition, the change in energy values and expected position with respect to time was calculated. The trends in the relaxation rate of electrons and holes were analyzed by studying their dependence on the initial excitation energy and temperature. This work provides computational evidence to support the original hypothesis that electron relaxation rates follow a band gap.